THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ENHANCING THE TRAVEL EXPERIENCE FOR TOURISTS: AN ANALYSIS OF SUCCESSFUL MODELS - Fatima Zohra BENBRAHMI; Hadj M’hammed MEHOR (Business Excellence and Management)
The pace of adopting artificial intelligence (AI) is accelerating across various fields, and the travel and tourism sector is one of the most benefited from this technology. This article reviews the impacts of AI on the development of travel and tourism experiences, focusing on four model countries: Switzerland, Egypt, Saudi Arabia, and the smart city of Helsinki, Finland. The article highlights the challenges faced by the tourism sector in improving service quality and meeting travelers' expectations in the modern technological era. The significance of this research is highlighted by its emphasis on how AI can be used as an innovative tool to enhance travel experiences and increase the efficiency of tourism operations. The article aims to explore practical applications of AI in these countries and provide insights into best practices that can be adopted in the sector. Through the analysis of successful models, the article arrives at several key findings: First, AI technologies contribute to the personalization of services according to travelers' needs, thereby increasing their satisfaction. Second, big data enables the analysis of customer behavior and the improvement of marketing strategies. Third, technological innovations enhance operational efficiency and reduce costs. The article concludes by offering future insights on how to leverage AI to achieve further innovation and growth in the travel and tourism industry, emphasizing the importance of international collaboration in knowledge and experience exchange to develop the tourism sector for optimal results.